Heat pipes as a passive cooling system for flywheel energy storage application. (March 2019) - Tetuko, A P; Hadi, R K; Faqih, M; Setiadi, E A; Kurniawan, C; Sebayang, P
Abstract: In this research, the effects of the heat pipes arrangement as a passive cooling system in an electric motor for the flywheel energy storage application were analysed. Two heat pipes variations were used and attached to the outer surface of the electric motor, 4 and 6 heat pipes arrangements, respectively. The test was also compared with the condition where no heat pipes attached. A numerical model was developed to simulate the temperature distribution on the electric motor. An analytical model was also used to calculate the effect of the fin length to the heat transfer capability of the heat pipes. The test result suggested that the heat pipes can be used as a passive cooling system and could reduce the temperature on the surface of the electric motor significantly. The arrangement with 6 heat pipes has the highest temperature reduction from 50 to 35 °C as compared to other conditions. The numerical simulation has a good agreement with the experimental results conducted in the laboratory and was used as validations for the model. The analytical model suggested that the increase of the fin length in one heat pipe affects the heat transfer surface area and thus the heat dissipation can be enhanced.